Rethoric, Literary Criticism and Canon in Quintilian, Institutio Oratoria 10.1 - Iribarren, Verónica (AADEC - UNL, 2016)
The literary canon implies a systematic and hierarchic selection of writers, works and genres in order to delimit an imitable model corpus connected to thepedagogic instruction. This paper analyzes the particular process of formation and conformation of the canon –as well as its reception and transformation fromprevious canons– established by Quintilian in the Book 10 of his Institutio Oratoria, in order to demonstrate that the criteria of selection that guide the canon exceed the mere didactic function.